The Dual Pathways of Job Demands and Resources, and the Role of Work Engagement as a Mediator of Innovative Work Behaviour in Indonesian Startups - Rahma, Dyvanka; Wiyono, Arsyadhira Adjani; Prasetya , Agustian Budi (Syntax Corporation, 2025)
This study examines the factors that influence Innovative Work Behaviour (IWB) among employees in Indonesian startups with Flexible Work Arrangements (FWA). Job demands (JD), job resources (JR), and work engagement (WE) were examined for their influence on innovative work behaviour (IWB). Data collection techniques included a survey of 258 startup employees undergoing FWA. Data processing techniques utilise SmartPLS 4.0, and sampling techniques were convenience. The results of the study accepted the hypothesis that job demands (JD) have a negative effect on work engagement (WE), while JD is not related to IWB; hence, this hypothesis was rejected. Conversely, JR has been proven to have a positive effect on both WE and IWB, and all related hypotheses are accepted. In addition, WE also has a positive effect on IWB. This study concluded that the innovative behaviour of employees in Indonesian startups, under flexible working arrangements, is influenced by work engagement (WE). Employee work engagement, under flexible working arrangements, also functions as a full mediating factor on the influence of job demands on innovative behaviour, and a partial mediating factor on the influence of job resources on employees’ innovative behaviour. These findings confirm the JD-R theory in explaining employee innovative behaviour, highlighting the importance of managing employee work engagement (WE) to address the challenges of an uncertain organisational environment in Indonesian startups.